The Detection of Active Compounds in the Methanolic Crude Extract of Euphorbia Tirucalli Stems - Reyam J. Mahmood; Abbas A. mohammed Al- Janabi (Engineering and Technology Journal, 2016)
This study was carried out to detect the active compounds existing in the methanolic crude extract of Euphorbia tirucalli stems by chemical reagents and solutions. The results revealed that the methanolic extract of E.tirucallistems contains Alkaloids, Phenols, Tannins, Flavonoids, Terpens, Steroids, Saponins, Resins, Saccharides, Coumarins, and volatile oils. From this, it could be concluded that E.tirucalli should be considered as a promising medicinal plant, because of its content of active compounds especially phenols and flavonoids which are known by their medicinal properties, especially the antioxidant property.